2009
DOI: 10.1177/1758834009348984
|View full text |Cite
|
Sign up to set email alerts
|

Review: Beyond KRAS: perspectives on new potential markers of intrinsic and acquired resistance to epidermal growth factor receptor inhibitors in metastatic colorectal cancer

Abstract: The monoclonal antibodies cetuximab and panitumumab, directed against the epidermal growth factor receptor (EGFR), are licensed for the treatment of KRAS wild-type metastatic colorectal cancer (mCRC). Such 'molecular restriction' derived from post-hoc analyses of randomized trials and from other retrospective series all indicate how tumors bearing KRAS (v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog) mutations are resistant to EGFR inhibition. Even if highly sensitive for nonresponse, KRAS testing is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…These angiogenic mechanisms involved in resistance to anti-EGFR agents include increased expression of VEGF and other VEGFR-1 ligands. Despite this intriguing preclinical evidence, phase III randomized trials did not find benefit from combined inhibition of EGFR and VEGF pathways [ 95 - 98 ].…”
Section: Preclinical and Translational Findings About Ras-related Acqmentioning
confidence: 99%
“…These angiogenic mechanisms involved in resistance to anti-EGFR agents include increased expression of VEGF and other VEGFR-1 ligands. Despite this intriguing preclinical evidence, phase III randomized trials did not find benefit from combined inhibition of EGFR and VEGF pathways [ 95 - 98 ].…”
Section: Preclinical and Translational Findings About Ras-related Acqmentioning
confidence: 99%
“…Mutations of BRAF have been described in about 15% of all human cancers (Davies et al 2002 ). In contrast to melanoma or colorectal cancer (Loupakis et al 2009 ), these mutations are relatively rare events in HNSCC. In their series of 89 HNSCC, Weber et al reported only 3% with activating BRAF mutations (Weber et al 2003 ).…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, it has been suggested that CA-SSR1 has an effect on gene transcription. This hypothesis was tested in several cell lines ( 20 , 22 , 23 ) as well as in head and neck, lung, pancreas, colon and mammary tumours ( 17 20 , 34 , 35 ), but the results were inconsistent and somewhat contradictory, most likely due to the limited number of analysed samples. We found the same distribution of CA-SSR1 alleles in normal tissues as previously reported ( 18 , 28 , 36 ), and the most common genotype was 16/16.…”
Section: Discussionmentioning
confidence: 99%
“…One of these regions is the CA dinucleotide repeat polymorphism in intron 1 of the EGFR gene. CA-SSR1 is important due to its close location to the second enhancer (15) which endows it with the ability to influence the expression of the EGFR gene (16)(17)(18)(19)(20)(21). Given that CA-SSR1 could modulate EGFR transcription, changes in its sequence could also alter the levels of EGFR protein.…”
Section: Introductionmentioning
confidence: 99%